Transplantation of mesenchymal stem cells for spinal cord injury: a systematic review and network meta-analysis - Chen, Wei-can; Liu, Wei-feng; Bai, Yu-yan; Zhou, Ying-ying; Zhang, Yan; Wang, Cong-mei; Lin, Shu; He, He-fan (Journal of translational medicine, 2021)
Spinal cord injury (SCI) is a severe traumatic disease of the central nervous system, with a global prevalence of 236–4187 per million people. This meta-analysis aimed to evaluate the safety and efficacy of mesenchymal stem cells (MSCs) in treating patients with SCI as well as the optimal source and transplantation method of MSCs. PubMed, OVID, Cochrane, Web of Science, and China Biomedical Database were searched up until April 01, 2021. The study was conducted for five endpoints: American Spinal Injury Association (ASIA) motor and sensory score, ASIA grade improvement, Barthel Index (BI), and adverse reactions. Standard meta-analysis and network meta-analysis were performed using Stata 14.0. Eighteen studies with a total of 949 patients, were included in the meta-analysis. Standard meta-analysis showed that MSCs significantly improved ASIA motor score (P < 0.001), sensory score (P < 0.001), ASIA grade (P < 0.001), and BI (P < 0.001) compared to rehabilitation. In addition, in the network meta-analysis, autologous MSCs significantly improved the ASIA motor [MD = 8.01, 95% CI (4.27, 11.76)], sensory score [MD = 17.98, 95% CI (10.04, 25.91)], and BI [MD = 7.69, 95% CI (2.10, 13.29)] compared to rehabilitation. Similarly, compared to rehabilitation, intrathecal injection (IT) of MSCs significantly improved the ASIA motor [MD = 7.97, 95% CI (4.40, 11.53)] and sensory score [MD = 19.60, 95% CI (9.74, 29.46)]. Compared to rehabilitation, however, only the IL of MSCs was associated with more adverse reactions [OR = 17.82, 95% CI (2.48, 128.22)]. According to the results of SUCRA, both autologous MSCs and IT transplantation approaches most improved the neurological function in SCI patients. Cell transplantation using MSCs is effective in patients with SCI and IT of autologous MSCs may be more beneficial.